Aortic “Disease-in-a-Dish”: Mechanistic Insights and Drug Development Using iPSC-Based Disease Modeling - Davaapil, Hongorzul; Shetty, Deeti K.; Sinha, Sanjay (Frontiers in Cell and Developmental Biology, 2020)
Thoracic aortic diseases, whether sporadic or due to a genetic disorder such as Marfan syndrome, lack effective medical therapies, with limited translation of treatments that are highly successful in mouse models into the clinic. Patient-derived induced pluripotent stem cells (iPSCs) offer the opportunity to establish new human models of aortic diseases. Here we review the power and potential of these systems to identify cellular and molecular mechanisms underlying disease and discuss recent advances such as gene editing and smooth muscle cell embryonic lineage. In particular, we discuss the practical aspects of vascular smooth muscle cell derivation and characterization, and provide our personal insights into the challenges and limitations of this approach. Future applications, such as genotype-phenotype association, drug screening and precision medicine are discussed, and we propose that iPSC-derived aortic disease models could guide future clinical trials with ‘clinical-trials-in-a-dish’ paving the way for new and improved therapies for patients.